Soil Quality in Agroecological Production Areas in Southern Brazil: Indicators Based on Farmers’ Perception - Chies, acir João; Casalinho, Helvio Debli; Stumpf, Lizete; Pinto, Marília Alves Brito; Júnior, Leonir Aldrigui Dutra (Journal of Agricultural Studies, 2021)
Farmers’ local knowledge about soil quality and management practices should be considered to assess the impact of agricultural technology packages on the environmental performance of agro-ecosystems. This study aimed to evaluate the soil quality under agroecological production in southern Brazil, which was considered of good quality by the farmers’ perception. From August to November 2017, ten farms from Liberdade settlement were visited, and semi-structured interviews were conducted to collect information about soil and agricultural knowledge. “What does good quality soil mean? What cares for preserve soil quality? Does the soil location in landscape influence conservation practices?” were the questions asked. In May 2018, soil samples were collected from each area, and chemical, physical, and biological attributes were determined. All farmers mentioned the organic matter indicated good soil quality; however, the study showed that most soils have low content, a consequence of the annual tillage adopted by all farmers for the implantation of seeds crops; Farmers indicated that a good quality soil has "life" with the presence of organisms. In our study, a low population of mites and springtails in most areas was observed. Positive farmers’ perception about the organic matter content and soil organism’s presence in their agroecological production areas come from the degradation history of the areas, at the same time that they attribute improvements in soil quality due to the actions adopted over the 10 years of agroecological production.